Diagnosis and Management of Bleeding Vitreous by Trauma Closed Eyeball - Rika Anggraini; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2019)
Introduction. Diagnosis of vitreous bleeding is generally straightforward and it can be made through history, ophthalmological examination and fundoscopy. However, the management is determined by the underlying etiology. The most common causes as factors that cause opposite vitreous bleeding include retinopathy of proliferative diabetes, posterior vitreous detachment (PVD) and trauma in 59-88.5% of cases. Reported a case of vitreous hemorrhage due to closed eyeball trauma performed by pars plana vitrectomy and endolaser with significant vision improvement. Case Presentation. A male, 21 years old, student, lived in suburban, came to the Polyclinic of RSMH on July 2019. Approximately 1 month ago the patient complained that his right eye vision suddenly felt blurry after being hit by volleyball from the front from a distance of 1 meter while playing volleyball with his friends. Patients complain of the view of the right eye as if it were covered with a red shadow accompanied by pain around the right eye. Ophthalmological examination obtained vision of this patient is a wave of the hand that is 1/300 in the right eye and 6/6 in the left eye that shows the disorder is unilateral with a fairly poor decrease in vision. During intraoperative right eye hemorrhage was found to nearly cover the retina with the source of bleeding in peripheral retinal blood vessels which when found intraoperatively were not found extravasation or active bleeding. Conclusion. The operative action of pars plana vitrectomy gives a clinically significant result that is obtained very good sharp eyesight and from the examination results obtained echofree on vitreous. Proper timing is very important in determining the management of vitreous bleeding in order to get good results and minimize the risk of complications that can occur.